LAW ENFORCEMENT OF THE CRIMINAL ACT OF EMBEZZLEMENT OF TIME DEPOSITS - KHRISTIYA LUTFIASANDHI (Universitas Islam Lamongan, 2021)
AbstractAn attitude of action or legal behavior usually has a certain influence when it relates to the behavior of other parties, an attitude of action or legal behavior is considered effective if the attitude or behavior of the other party leads to the desired goal, meaning whether the other party obeys the law. Criminal liability for future embezzlement by cooperative management is an act that is threatened with Article 374 of the Criminal Code because the cooperative management commits a crime by using the position as a cooperative manager, so that the manager who acts, the manager who is responsible, has the ability to be responsible and there is no excuse for forgiveness. .